One methyl group makes a major difference: Shape-selective catalysis by zeolite nanoreactors in liquid-phase condensation reactions - Liu, C.; Cao, C.; Liu, Jian; Wang, X.; Zhu, Y.; Song, W. (R S C Publications, 2017)
© 2017 The Royal Society of Chemistry. The precise sizes of zeolites' micropores can induce sharp shape/size-selectivity with precision of less than 1 Å in gas-phase reactions, e.g. methanol to olefin reactions (MTO). However, it is still a major challenge and an unachieved task in liquid-phase reactions. In this study, we demonstrate that shape-selectivity with one-methyl-group-precision can be realized in Knoevenagel condensation reactions on basic active sites encapsulated in zeolite crystals. Furthermore, Pd nanoparticles can also be introduced to the interior of hollow zeolite crystals, resulting in a multifunctional and shape-selective catalyst in a one-pot Knoevenagel condensation-hydrogenation cascade reaction.